2022
DOI: 10.1111/itor.13132
|View full text |Cite
|
Sign up to set email alerts
|

Managing bank performance under COVID‐19: A novel inverse DEA efficiency approach

Abstract: The evolution of the COVID‐19 pandemic is highly unpredictable; however, its impacts are limited to neither a single sector nor a single country. This study evaluates the performance and efficiency of 49 Islamic banks across 10 countries during 2019–2020 to assess how those banks can preserve their performance and remain resilient in the aftermath of the COVID‐19 pandemic. Using the conventional inverse data envelopment analysis (InvDEA) approach, we show that because of reductions in their outputs, 31 out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…One may also extend our study to a larger sample (e.g. using the BankScope database), different profitability and performance measurements such as technical or cost efficiency (Boubaker et al, 2022;Le et al, 2022b), and to other advanced methodologies such as the auto-regressive distributed lag (ARDL) with structural break, Bayesian or machine learning (Haans et al, 2016;Preciado Arreola et al, 2020;Zhao et al, 2020;Thaker et al, 2021). We look forward to such studies contributing to the literature on ESG and bank performance amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…One may also extend our study to a larger sample (e.g. using the BankScope database), different profitability and performance measurements such as technical or cost efficiency (Boubaker et al, 2022;Le et al, 2022b), and to other advanced methodologies such as the auto-regressive distributed lag (ARDL) with structural break, Bayesian or machine learning (Haans et al, 2016;Preciado Arreola et al, 2020;Zhao et al, 2020;Thaker et al, 2021). We look forward to such studies contributing to the literature on ESG and bank performance amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…Since the COVID-19 is an ongoing issue, and because of the data availability constraint (e.g., we could not collect data on bank ownership, or data on GDP and inflation were not available after 2020), we expect that future research could provide a more comprehensive analysis to strengthen our findings. One may also extend our study to a larger sample (e.g., using the BankScope database), different profitability and performance measurements such as technical or cost efficiency (Boubaker et al, 2022;Le et al, 2022b), and other advanced methodologies such as the auto-regressive distributed lag (ARDL) with structural break, Bayesian or machine learning (Haans et al, 2016;Preciado Arreola et al, 2020;Zhao et al, 2020;Thaker et al, 2021). We look forward to such studies contributing to the literature on ESG and bank performance amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been adopted across several disciplines, one of which is business and finance research. Boubaker et al (2022) and Vidal-García et al (2018) adopted the DEA approach in their studies and found it suitable for examining efficiency.…”
Section: Introductionmentioning
confidence: 99%